We just started a new unit and the instructor hasnt explain how to do this even thoug i can tell its simple

Findf'(a).

f(x) = √(3x+ 1 )

Results 1 to 3 of 3

- Sep 19th 2008, 12:49 PM #1

- Joined
- Sep 2008
- Posts
- 1

- Sep 19th 2008, 01:13 PM #2

- Sep 19th 2008, 03:19 PM #3
Note that Matt's answer comes from writing the function as $\displaystyle (3x + 1)^{\frac 12}$ and applying the chain rule

the chain rule says: $\displaystyle \frac d{dx}f(g(x)) = f'(g(x)) \cdot g'(x)$

here, $\displaystyle f(x) = x^{\frac 12}$ and $\displaystyle g(x) = 3x + 1$